Social Corporate Responsibility regarding Household Consumer Satisfaction with the Electric Power Supply Services - Maria-Ana Georgescu; Emilia Herman (Amfiteatru Economic)
The issue of the practical manifestation of corporate social responsibility towards consumers is highly important to the socio-economic reality in Romania. The present paper is the result of an investigation carried out in this field and it is distinguished by two aspects. The first aspect is its target audience used for research - household consumers of electricity, who can be called "vulnerable", captive consumers. The second aspect is the specificity of the electricity market. The aim of the research was to study the relationship between corporate social responsibility, instantiated by the quality of services provided by S.C. Electrica S.A. – Electrica Distribution and Supply South Transylvania and the consumers' loyalty towards the company, in case other electricity suppliers emerge. A subsidiary aspect was the generation of a database having an impact on customer retention. We have carried out some quantitative research, based on the survey method, having a sample of 521 household consumers from the Mures County. The study we carried out proves that consumer satisfaction, their degree of satisfaction under different aspects, is a way of gaining their trust on this particular market. Those consumers with a higher degree of trust in the company are more loyal. This will result in reducing migration to another electricity supplier, in the future, when all household consumers become eligible.